(3TQM GdTQGFY aj CaYGd GdUdGIs - (3GdeGRfOQGfj, eMeO GdeGRfOQGfj, eMeO Ydj Hf ebUhO Ydj, J (B1264(3g` (B1848(3es ((3HNW GdeDdas)
(3ChdgG (B:s
(3ChdgG(B: (3HfbU GdJcHjQ aj GdHSeJjf GdChdJjf bGFdg GdTjN aj GdeHShW (B.. (3hYed jhe hdjdI hYf eUHGM GdSjOI (B.. (3haj GdZfjI hGdeQGSe hMcGg ajs
(3BNQgG (B:s
(3BNQgG(B: (3GdeNJU HGdLeYI bHd GdQchY aj GdChdi (B.. (3hgPG CNHGQ GdKGfj Ydi (B... (3djS EdG Yehe GdCNHGQ HGSJMHGH bfhJ (B.. (3GdKGfjI bHd GdQchY hajg Cfg eNUU HLejY GdCNHGQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3eYLe GdeDdajf, L(B3: 549s
(3GdPQjYI, L (B18: 7s
(3eUOQ GbJfGA GdCUd (B:s
(3cGTa GdZWGAs
(3ehGUaGJ GdhYGA (B:s
Keywords: (3abg GdePGgH GdCNQis